From Threat to Relief: Expressing Prejudice toward Atheists as a Self-Regulatory Strategy Protecting the Religious Orthodox from Threat - Kossowska, Małgorzata; Szwed, Paulina; Czernatowicz-Kukuczka, Aneta; Sekerdej, Maciek; Wyczesany, Miroslaw (Frontiers in Psychology, 2017)
We claim that religious orthodoxy is related to prejudice towards groups that violate important values, i.e., atheists. Moreover, we suggest that expressing prejudice may efficiently reduce the threat posed by this particular group among people who hold high levels, but not low levels, of orthodox belief. We tested these assumptions in an experimental study in which, after being exposed to atheistic worldviews (value-threat manipulation), high and low orthodox participants were allowed (experimental condition) or not (control condition) to express prejudice towards atheists. Threat was operationalized by cardiovascular reactivity, i.e., heart rate (HR); the higher the HR index, the higher the threat. The results found that people who hold high (vs. low) levels of orthodox belief responded with increased HR after the threat manipulation. However, we observed decreased HR after the expression of prejudice towards atheists among highly orthodox participants compared to the control condition. We did not find this effect among people holding low levels of orthodox belief. Thus, we conclude that expressing prejudice towards this particular group may be an efficient strategy to cope with the threat posed by this group for highly orthodox people. The results are discussed in light of previous findings on religious beliefs and the self-regulatory function of prejudice.